Healthcare Ethics Among Resident physician and Ward Nurses of Obstetrics and Gynaecology Department in Tobruk Medical Centre - Tobruk -Libya - Eshail, Asmaa.M. (Aljameai, 2024)
Abstract: Healthcare ethics is deserted in clinical practice among medical staff in Low and Middle Income Countries such as Tobruk in Libya. This study to assess and compare the level of knowledge, attitudes and practices of medical resident physicians and nurses in Tobruk Medical Centre. This study, carried out on 35 resident physicians and 31 ward nurses in the teaching hospital of Tobruk in May 2022 with a self-administered questionnaire. Results: Our study demonstrated that a significant proportion of the physicians and nurses were unaware of major documents of healthcare ethics: Hippocratic Oath, Nuremberg code and Helsinki Declaration. A high percentage of respondents said that their major source of information on healthcare ethics were I, Attitude of physicians and nurses were significantly different to different aspects of healthcare ethics. More nurses had agreement than physicians on if there is disagreement between patient and families and health care professionals about treatment decision physicians decision should be final (100 % physicians versus 90.3 % nurses),and both have interesting to learning health care ethic (100% physicians versus 90.3% nurses). Only (54.8 % physicians and nurses) agree to patient wishes must always adherent to. Conclusions: The study showed that there was inadequate as well as a non-uniform level of knowledge of three major codes of medical ethics and principles related to it which resulted in significant disparity in the attitude and practice of medical ethics among physician and nurses in Obstetrics and Gynaecology Department in Tobruk Medical Centre 1 المستخلص: يلاحظ ان أخلاقيات الرعاية الصحية في الممارسة السريرية يتم تجاهلها وعدم العمل بها بين الطاقم الطبي في البلدان المنخفضة والمتوسطة الدخل مثل طبرق في ليبيا. يهدف هذا البحث إلى تقييم ومقارنة مستوى المعرفة والاتجاهات والممارسات للأطباء والممرضين المقيمين في مركز طبرق الطبي. هذه دراسة مقطعية، أجريت على 35 طبيبًا مقيمًا و31 ممرضًا في مستشفى طبرق التعليمي في مايو 2022 باستخدام استبيان ذاتي. أظهرت دراستنا أن نسبة كبيرة من الأطباء والممرضات لم يكونوا على علم بالوثائق الرئيسية لأخلاقيات الرعاية الصحية: قسم أبقراط (63% من الأطباء و16% من الممرضات كانوا على علم بذلك)، وقانون نورمبرغ وإعلان هلسنكي (11% من الأطباء والممرضين كانت الممرضات على علم). قالت نسبة عالية من المشاركين أن المصدر الرئيسي لمعلوماتهم حول أخلاقيات الرعاية الصحية هو أنا (77.5% أطباء من المؤتمرات مقابل 71.4% ممرضات من المحاضرات)، (31.4% أطباء مقابل 22.6% ممرضات من المحاضرات)، يلاحظ ان سلوك الأطباء والممرضات كانت مختلفة بشكل كبير في جوانب مختلفة من أخلاقيات الرعاية الصحية. كان عدد الممرضات أكثر من الأطباء بشأن ما إذا كان هناك خلاف بين المريض وأسرته ومتخصصي الرعاية الصحية حول قرار العلاج، يجب أن يكون قرار الأطباء نهائيًا (100% أطباء مقابل 90.3% ممرضات)، وكلاهما مثير للاهتمام لتعلم أخلاقيات الرعاية الصحية (100% أطباء) مقابل 90.3% ممرضات). فقط (54.8% من الأطباء والممرضين) يوافقون على رغبات المريض ويجب الالتزام بها دائمًا الاستنتاج:. أظهرت الدراسة أنه لا يوجد مستوى كاف وغير منتظم من المعرفة لثلاث قواعد رئيسية لأخلاقيات الطب والمبادئ المتعلقة بها مما أدى إلى تباين كبير في المواقف والممارسة لأخلاقيات الطب بين الأطباء والممرضين في طب التوليد. وقسم أمراض النساء بمركز طبرق الطبي.